The impact of parenting styles on adolescents' behavior among muslim families in Yala province, Southern Thailand - Pairoh, Hasanah (Institute of Education, International Islamic University Malaysia, 2011)
This study analyzed the impact of parenting styles on adolescents' behavior. Firstly, it aimed at investigating the nature of parenting styles practiced by Muslim families in Southern Thailand. It also determined the predictors of the following factors, namely parent's educational background, parent's occupation, type of family and home location. Secondly, this study aimed at investigating the adolescents' behavior among the youth in southern Thailand. It also determined the predictors of the following factors, namely gender, age and level of study. Lastly, the study explored the relationship between parenting styles and adolescents' behavior. The present research used a modified questionnaire, firstly, the parents' questionnaire was adopted and adapted from Robinson, Robinson, Mandleco, Olsen, and Hart (1995), while adolescents' behavior questionnaire was adopted and adapted from Silman (2005). The questionnaire was administered to 200 parents and 200 adolescents in Yala province, southern Thailand. Descriptive and multiple regression analysis were administered. This study found that the majority of parents in Yala province, southern Thailand used the authoritative parenting style. The best predictor was parent's educational background. Besides, the nature of adolescents' behavior in southern Thailand is more likely to practice pro-social behavior as opposed to anti-social behavior. Moreover, the study found that the relationship between parenting styles and adolescents' behavior, indicated that the authoritative and authoritarian parenting styles are related to pro-social behavior. Besides, anti-social behavior shows a relationship with permissive parenting style.